Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ma12193255
|View full text |Cite
|
Sign up to set email alerts
|

Promoted Anodizing Reaction and Enhanced Coating Performance of Al–11Si Alloy: The Role of an Equal-Channel-Angular-Pressed Substrate

Abstract: In this paper, the effect of the equal-channel-angular-pressed (ECAPed) substrate on the coating formation and anticorrosion performance of the anodized Al–11Si alloy was systematically investigated. The ECAP process dramatically refines both Al and Si phases of the alloy. The parallel anodizing circuit is designed to enable a comparative study of anodizing process between the cast and the ECAPed alloys by tracking their respective anodizing current quota. The optimum coatings of both alloys were obtained afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…Figure 5 illustrates the EIS Bode plots (Figure 5a) and Nyquist plots ( Figure 5b) after immersion in 3.5 wt.% NaCl solution for 1 h. Coated samples showed three time constants in the Bode plots, including two capacitive peaks in the high/middle frequencies and one capacitive peak in the low frequency. Double peaks (as marked by the two blue arrows in Figure 5a) are the typical EIS characteristics for coated samples, of which one peak relates to the single response from the coating/substrate interface and one peak relates to the response from the coating [42,43]. In this study, a third capacitive peak was also found, which may relate to the single response from the outer porous layer of the anodizing coating.…”
Section: Microstructure Characteristicssupporting
confidence: 53%
“…Figure 5 illustrates the EIS Bode plots (Figure 5a) and Nyquist plots ( Figure 5b) after immersion in 3.5 wt.% NaCl solution for 1 h. Coated samples showed three time constants in the Bode plots, including two capacitive peaks in the high/middle frequencies and one capacitive peak in the low frequency. Double peaks (as marked by the two blue arrows in Figure 5a) are the typical EIS characteristics for coated samples, of which one peak relates to the single response from the coating/substrate interface and one peak relates to the response from the coating [42,43]. In this study, a third capacitive peak was also found, which may relate to the single response from the outer porous layer of the anodizing coating.…”
Section: Microstructure Characteristicssupporting
confidence: 53%
“…By adding Mn to Al-4.6Mg alloys may produce grain refinement and dispersion strengthening, increasing tensile strength and hardness. The effect of the equal-channel-angular-pressed substrate on the coating formation and anticorrosion performance of the anodized Al-11Si alloy was investigated [9]. The procedure refines both Al and Si phases of the alloy.…”
mentioning
confidence: 99%